2021
DOI: 10.1007/s43546-021-00128-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of structure and culture on organizational performance: the case of Uganda’s High Court

Abstract: Despite many attempts to improve the performance of public sector organizations, in developing countries many such organizations are still underperforming. This study evaluates the impact of organizational structure and culture on the performance of Uganda's High Court by applying the high-performance organizations (HPO) framework. A questionnaire on the quality of the organizational structure, culture, and HPO status was distributed among High Court staff and the collected data were subjected to factor/regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Performance information plays a vital role in enabling managers to evaluate an organization's progress or regression. When evaluating organizational performance, factors such as reliability, competency, and collaboration among various functional units need to be taken into consideration (Kintu & de Waal, 2021).…”
Section: Organizational Performancementioning
confidence: 99%
“…Performance information plays a vital role in enabling managers to evaluate an organization's progress or regression. When evaluating organizational performance, factors such as reliability, competency, and collaboration among various functional units need to be taken into consideration (Kintu & de Waal, 2021).…”
Section: Organizational Performancementioning
confidence: 99%
“…In addition, it is shown that organizational structure has a significant impact on the performance of organizations independently of their size and sector (Iranmanesh et al , 2021; Amiri et al , 2017). It is also revealed that organizational structure significantly impacts the performance of public organizations (Kintu and de Waal, 2021). In the same vein, societal performance has an important effect on economic performance (Sila and Cek, 2017), which is essential for the global performance of an organization (Savall and Zardet, 2020).…”
Section: Conceptual Reviewmentioning
confidence: 99%
“…Regionally Kintu and de Waal did a study that evaluated the impact of organizational structure and culture on the performance of Uganda's High Court by applying a highperformance organizations (HPO) framework [26]. A questionnaire on the quality of the organizational structure, culture, and HPO status was distributed among High Court staff and the collected data were subjected to factor/regression analyses.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%